THE COMMUNICATION PATTERNS OF THE JUNAIDIYAH THARĪQAH (SUFI ORDER) IN THE CASE OF THE RELOCATION OF SHAIKH MUHAMMAD QURTHUBI'S TOMB IN PALANGKA RAYA - El Bilad, Cecep Zakarias; Zainab, Siti; Fatmah, Nor; Fadli, Syairil (al-Balagh : Jurnal Dakwah dan Komunikasi, 2024)
The relocation of the grave of Junaidiyah tharȋqah’s leader, Shaikh Muhammad Qurthubi, in Palangka Raya is unique. It was done without dismantling the old grave or moving his body. This unusual step was based on mystical messages from the shaikh’s spirit to his chosen students. This research explores why this action was taken and how this mystical doctrine became the community's shared belief. It is a qualitative study, and data were collected through interviews and observation using a phenomenological approach. The research findings are analyzed using theories of group communication, ritual communication, and the psychology of communication. The results show that Junaidiyah tharȋqah is a primary group with norms and doctrines that members must follow, determining their communication patterns. These patterns tend to be one-way in matters of teachings and spirituality and multidirectional in administrative and institutional matters. Interpersonal communication is intimate and solid. The research implies that the Junaidiyah tharȋqah's mystical doctrines deeply influence their members' communication patterns, fostering unwavering spiritual loyalty and shaping unique interpersonal and group communication dynamics.